2009
DOI: 10.1007/s12016-009-8143-0
|View full text |Cite
|
Sign up to set email alerts
|

The Premenstrual Syndrome and Fibromyalgia—Similarities and Common Features

Abstract: The aim of the study was to assess the clinical similarities and common features of fibromyalgia syndrome (FM) and premenstrual dysphoric syndrome (PMDD). Thirty young patients who met the diagnostic criteria for PMDD were included in the study and compared to 26 women belonging to the medical staff of a general psychiatry department. All enrollees were interviewed and examined by a skilled physician. They completed the following nine survey items: demographic information, clinical health assessment questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In these studies, the pain sensitivity to various stimuli in different phases of the menstrual cycle was evaluated in women with and without dysmenorrhea. The pain threshold against pressure, 13 heat, 14 and electricity 15 were reduced in the abdomen, back, and extremities in the menstrual phase in dysmenorrheic patients, whereas it increased against cold. In one study, increased amplitude by CO2 laser evoked cerebral potential in these patients.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In these studies, the pain sensitivity to various stimuli in different phases of the menstrual cycle was evaluated in women with and without dysmenorrhea. The pain threshold against pressure, 13 heat, 14 and electricity 15 were reduced in the abdomen, back, and extremities in the menstrual phase in dysmenorrheic patients, whereas it increased against cold. In one study, increased amplitude by CO2 laser evoked cerebral potential in these patients.…”
Section: Discussionmentioning
confidence: 85%
“…26 Chae et al 27 found a reduction in the pressure pain threshold at acupuncture points in the women with high symptom severity scores in premenstrual syndrome compared to those with low scores. Amital et al 15 investigated the similarities between premenstrual dysphoric disorder and FM syndrome, and found higher levels of tender points and higher rates of psychiatric comorbidities in the patients with PMS. Five of 30 patients with premenstrual dysphoric disorder were diagnosed with FM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We attributed the unexpected low prevalence of FMS in healthy controls to their younger ages. In accordance to the higher level of tenderness in PD patients, Amital et al (26) assessed the clinical similarities and common features of FMS and premenstrual dysphoric syndrome and reported that patients with premenstrual syndrome were found to have higher levels of TePs.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is not associated with genuine tissue inflammation and the etiology of the disorder remains poorly understood. FM patients report increased sensitivity to diverse stimuli among them also nociceptive input, which via different mechanisms converge to hypersensitize the central nervous system and in many manners are similar to patients with post-traumatic stress disorder, depression and other affective conditions [19][20][21][22][23][24][25][26]. Among other characteristics FM patients tend to report enhanced olfactory acuity [27].…”
Section: Introductionmentioning
confidence: 99%